Knowledge, attitude and practice regarding constipation in pregnancy among pregnant women in Shanghai: a cross-sectional study - Lin, Lin; Yu, Yi; Gu, Weirong; Hu, Rong; Zhu, Hao (Frontiers in Public Health, 2024)
Objective: This study aims to investigate the Knowledge, Attitude, and Practice (KAP) pertaining to constipation during pregnancy among pregnant women in Shanghai.Methods: Demographic data and KAP scores were collected using a questionnaire. Differences across groups were analyzed using either Wilcoxon-Mann-Whitney tests or Kruskal-Wallis analysis of variance. Spearman's correlation analysis was utilized to evaluate the relationships between KAP scores. Multivariable logistic regression analyses were conducted to identify factors that influence KAP scores.Results: Encompassing 241 individuals (46.6%) aged between 30 and 34 years, with 349 participants (67.5%) being nulliparous. The median scores for knowledge (possible range: 0 -26), attitude (possible range: 7 -35), and practice (possible range: 14 -70) were 22 (18, 24), 26 (23, 29), and 51 (46, 56), respectively. Multivariate analysis indicated that being a medical professional (OR = 2.222, P = 0.043) and receiving education on constipation during pregnancy (OR = 0.432, P<0.001) were significantly associated with higher knowledge scores. Factors significantly associated with practice included being aged 30-34 years (OR = 2.745, P < 0.001), aged 35 years and above (OR = 2.514, P < 0.001), working in education (OR = 2.310, P = 0.012), and not experiencing constipation before pregnancy (OR = 1.894, P = 0.001).Pregnant women demonstrated satisfactory knowledge, positive attitudes, and proactive practices concerning constipation during pregnancy. To further augment clinical practice, healthcare providers should tailor educational interventions and guidance specifically for pregnant women who are not medical professionals and those who have not received education and guidance related to constipation during pregnancy.